Joint Analysis of the DRD5 Marker Concludes Association with Attention-Deficit/Hyperactivity Disorder Confined to the Predominantly Inattentive and Combined Subtypes - GILL, MICHAEL; HAWI, ZIARIH (My University, 2004)
Attention-deficit/hyperactivity disorder (ADHD) is a highly heritable, heterogeneous disorder of early onset, consisting of a triad of symptoms: inattention, hyperactivity, and impulsivity. The disorder has a significant genetic component, and theories of etiology include abnormalities in the dopaminergic system, with DRD4, DAT1, SNAP25, and DRD5 being implicated as major susceptibility genes. An initial report of association between ADHD and the common 148-bp allele of a microsatellite marker located 18.5 kb from the DRD5 gene has been followed by several studies showing nonsignificant trends toward association with the same allele. To establish the postulated association of the (CA)n repeat with ADHD, we collected genotypic information from 14 independent samples of probands and their parents, analyzed them individually and, in the absence of heterogeneity, analyzed them as a joint sample. The joint analysis showed association with the DRD5 locus (P=.00005; odds ratio 1.24; 95% confidence interval 1.12?1.38). This association appears to be confined to the predominantly inattentive and combined clinical subtypes.
PUBLISHED
PMID: 14732906
Keywords: Psychiatry